Traitement des plaintes d'agression sexuelle envers les enfants dans le système de justice criminel québécois - Alonzo-Proulx, Agnès (Canadian journal of criminology and criminal justice, 2017)
Our understanding of the criminal process of child sexual abuse (CSA) cases in the province of Québec remains limited. In order to better determine the variables linked to the investigators' decision to substantiate the complaint and the district attorney's to authorize its proceeding in court, characteristics of the child, sexual abuse, shared custody, disclosure context, available evidence, and investigative interviews were collected from 169 CSA police files and interview transcripts. Results from the logistic regressions show some common predictors at both professionals' levels in their decision to accept the file: the child's age and the suspect's corroboration. At the investigators' level, additional predictors were significant in finding the case substantiated: an accidental disclosure, the choice of the first person who received the disclosure, and the frequency of the abuse. At the district attorneys' level, additional significant predictors were the protection offered by the mother following her child's disclosure, the use of a non-suggestive interview protocol, and the corroboration of the witness. These results underline the importance of variables linked to the evidence's strength but also point to the interest of justice and complainant, such as the maternal protection, as predictors of court involvement in CSA cases.